Development of an Atlas of Mangrove Plant Morphology Based on the Local Potential of PPLH Puntondo Takalar as a Supplementary Teaching Material for the Plantae Topic in Grade 10 Senior High School - Nurul Akma; Ummul Hasanah; Misykat Malik Ibrahim (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to develop a mangrove plant morphology atlas based on the local potential of the Puntondo Takalar Center for Environmental Education (PPLH Puntondo Takalar) as a supplementary teaching material for the Grade 10 high school Plantae topic that meets the criteria of validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects comprised 26 Grade 10 students and one biology teacher in a limited trial conducted at a senior high school in Takalar Regency. Data were collected through observation, interviews, needs analysis questionnaires, expert validation sheets, response questionnaires, and learning outcome tests. The results showed that the developed atlas included nine mangrove species identified through field observations, presented systematically based on morphological characteristics and distribution locations. The atlas was supplemented with field photographs, identification keys, distribution maps, and observation tasks that support environment-based learning and scientific literacy. Expert validation results yielded an average score of 3.6, categorized as highly valid. The practicality test indicated a positive response rate of 92% from both the teacher and students, categorized as highly practical. The effectiveness test showed that classical learning mastery reached 100%, with all students achieving scores above the minimum mastery criterion (KKM). Therefore, this mangrove plant morphology atlas based on local potential is feasible for use as a supplementary teaching material and has the potential to support contextual biology learning while enhancing students’ biodiversity literacy.